Conjunctival cytology assessment in dogs and cats. Sampling, diagnostic techniques and findings - ATHANASIOU, L. V.; PSEMMAS D. Ε.; PAPAIOANNOU, N. (Journal of the Hellenic Veterinary Medical Society, 2018)
The conjunctiva provides a physical and physiological barrier against microorganisms and foreign bodies and also contributes to the ocular immunological defense. It constitutes a straightforward and accessible tissue for sampling and examination. Sampling indications include: changes in color, surface irregularities, thickening, or masses, ocular discharge and the identification of infectious organisms. Samples for conjunctival evaluation may be collected with exfoliative or abrasive techniques, aspiration, impression and conjunctival biopsy. The most commonly used and clinically useful laboratory methods for the assessment of conjunctival specimens are: microscopic examination of cytological preparations, culture and susceptibility testing, live virus isolation, polymerase chain reaction, direct immunofluorescent antigen test and histopathological examination for snip biopsies. Findings like inflammatory or neoplastic cells, cellular alterations, inclusion bodies and microorganisms, offer valuable information not only for localized ocular disorders, but for systemic diseases as well.